Fenomena wisata minat khusus berbasis pink tourism: studi kasus di M.Bar - Wullur, Sarah Geraldine; Suprapto, I Nyoman Arto; Pranatayana, Ida Bagus Gde (YAYASAN MITRA PERSADA NUSANTARA, 2022)
Bali as a global destination has been recognized by various people including the LGBT (Lesbian, Gay, Bisexual, Transgender) community. Despite being known for its cultural tourism, the pink tourism phenomenon exists and lives together along with the locals of Seminyak village. This research aims to discover the existence of pink tourism at M.Bar in Smk. as well as the perception of the locals and the government toward the happening phenomenon. This qualitative-descriptive research used snowball sampling to determine the population. The result shows that the pink tourism phenomenon exists due to the motivation from the LGBT community to aim for freedom of traveling without any discrimination toward them. Smk as a developing tourist area has a gay bar that is considered a safe place for the LGBT community and is called Mixwell Bar. This motivates the LGBT community to visit Seminyak in order to get the freedom they need. The government confirmed that pink tourism is not in line with cultural tourism in Bali. However, the locals see LGBT tourists as an economic stimulus through the tourism industry but do not acknowledge them to have legal behavior. The researchers hope that the information provided could be a consideration for Bali's tourism policy in the future.